Loropetalum axillare (Hamamelidaceae), a new species from Guangdong, China - Jin, Zi-Chao; Xu, Lian-Sheng; Xu, Ye-Chun; Chen, You-Sheng (Phytotaxa, 2023)
Loropetalum axillare (Hamamelidaceae), a new species from Zengcheng District, Guangzhou, Guangdong, China, is described and illustrated. The new species is related to Loropetalum chinense but differs by its inflorescence axillary and peduncle absent (vs. inflorescence terminal and peduncle 0.8–1 cm long). The new species is supported by phylogenetic analyses based on ITS and ETS sequences.